Ginsenoside Rg1 attenuates glomerular fibrosis by inhibiting CD36/TRPC6/NFAT2 signaling in type 2 diabetes mellitus mice. (10th February 2023) - Han, Yuli; Su, Yong; Han, Min; Liu, Yan; Shi, Qifeng; Li, Xuewang; Wang, Penghui; Li, Weiping; Li, Weizu
Abstract: Ethnopharmacological relevance: Ginsenoside Rg1 (Rg1) is one of the main active components in Panax ginseng C. A. Meyer (ginseng), which has been widely used to delay senescence or improve health conditions for more than 2000 years. Increasing studies have revealed that Rg1 could regulate cell proliferation and differentiation, as well as anti-inflammatory and anti-apoptotic effects, and might have protective effects on many chronic kidney diseases. Aim of the study: Diabetic nephropathy (DN) is one of the most dangerous microvascular complications of diabetes and is the leading cause of end-stage renal disease worldwide. However, the role and mechanism of Rg1 against high-glucose and high-fat-induced glomerular fibrosis in DN are not clear. This study aimed to investigate the protective effect of Rg1 on DN and its possible mechanism. Materials and methods: The type 2 diabetes mellitus (T2DM) mice models were established with a high-fat diet (HFD) combined with an intraperitoneal injection of streptozotocin (STZ). Urine protein and serum biochemical indexes were detected by corresponding kits. The kidney was stained with H&E, PAS, and Masson to observe the pathological morphology, glycogen deposition, and fibrosis. The expression of CD36 and p-PLC in the kidney cortex was detected by IHC. The expressions of FN and COL4 were detected by IF. Western blot and PCR were performed to examine protein and mRNA expressions of kidney fibrosis and TRPC6/NFAT2-related pathways in DN mice. Calcium imaging was used to examine the effect of Rg1 on [Ca 2+ ]i in PA + HG-induced human mesangial cells (HMCs). Visualization of the interaction between Rg1 and CD36 was detected by molecular docking. Results: Rg1 treatment for 8 weeks could prominently decrease urinary protein, serum creatinine, and urea nitrogen and downgrade blood lipid levels and renal lipid accumulation in T2DM mice. The pathological results indicated that Rg1 treatment attenuated renal pathological injury and glomerular fibrosis. The further results demonstrated that Rg1 treatment remarkably decreased the expressions of CD36, TRPC6, p-PLC, CN, NFAT2, TGF-β, p-Smad2/3, COL4, and FN in renal tissues from T2DM mice. Calcium imaging results found that Rg1 downgraded the base levels of [Ca 2+ ]i and ΔRatioF340/F380 after BAPTA and CaCl2 treatment. Molecular docking results showed that Rg1 could interact with CD36 with a good affinity. Conclusion: These results revealed that Rg1 could ameliorate renal lipid accumulation, pathological damage, and glomerular fibrosis in T2DM mice. The mechanism may be involved in reducing the overexpression of CD36 and inhibiting the TRPC6/NFAT2 signaling pathway in renal tissues of T2DM mice. Graphical abstract: Image 1 Highlights: Rg1 treatment ameliorates glomerular fibrosis and diabetic nephropathy in T2DM mice. Rg1 treatment decreases the levels of blood lipids and renal DAG and IP3 in T2DM mice. Rg1 treatment inhibits CD36 expression and PLC activation in T2DM mice. Rg1 treatment inhibits TRPC6/CN/NFAT2 signaling in T2DM mice.